Role of N-acetyl cysteine for the prevention of postendoscopic retrograde cholangio-pancreatography pancreatitis (BIRDEM Medical Journal, 2023)
Background: Pancreatitis is one of the common complications of endoscopic retrograde cholangiopancreatography (ERCP) procedure. Pathogenesis of acute pancreatitis is probably the capillary endothelial injury mediated by oxygen-derived free radicals. Different medications and procedures have been used to prevent post-ERCP pancreatitis (PEP) but are of little benefit. N-acetyl cysteine (NAC) is a safe free radical scavenger. The aim of this study was to evaluate prevention of PEP by inhibiting inflammatory intermediates and oxidative stress with NAC.Methods: This quasi-experimental study was carried out at the Department of Gastrointestinal, Hepatobiliary and Pancreatic Disorders (GHPD) of BIRDEM General Hospital, Dhaka, Bangladesh from January 2018 to July 2019. After meeting the eligibility criteria, total 150 candidates for ERCP were enrolled in this study. Patient lists were collected from ERCP procedure room and patients with uneven serial numbers were selected into the N-group who received a colorless solution of 1200 mg NAC (1200 NAC dissolved with 150 cc water) orally 2 h before ERCP and patients with even serial numbers were selected into the P-group who received only 150 cc water. Serum lipase was measured 2 times: at 4 hours and 24 hours after ERCP. Patients who developed PEP were also evaluated for the risk factors of PEP.Results: PEP occurred in 34 patients (22.6%) out of 150 study subjects [mild 20 (13.3%), moderate 13 (8.6%) and severe 1 (0.7%)]. From N-group 17 patients (22.6%) and from P-group 17 patients (22.6%) developed PEP (p value 0.577). Risk factor analysis revealed that the young age group, patients with type-2 diabetes (T2DM) getting insulin, difficult cannulations, injection of contrast into the pancreatic duct and trainee involvement in the procedure were statistically significant. In multivariate analysis, the young age group, patients with T2DM getting insulin and trainee involvement remained the risk factors of PEP.Conclusion: In conclusion, N-acetyl cysteine had no role in the prevention of PEP in this study.BIRDEM Med J 2023; 13(1): 38-43